Coseismic ruptures of the 24 August 2016, Mw 6.0 Amatrice earthquake (central Italy). Issue 5 (4th March 2017) - Pucci, S.; De Martini, P. M.; Civico, R.; Villani, F.; Nappi, R.; Ricci, T.; Azzaro, R.; Brunori, C. A.; Caciagli, M.; Cinti, F. R.; Sapia, V.; De Ritis, R.; et al.
Abstract: On 24 August 2016, a Mw 6.0 normal‐faulting earthquake struck central Italy, causing about 300 fatalities and heavy damage. A geological survey collected the coseismic effects observed at the surface in order to evaluate two competing hypotheses about their nature: surface faulting versus gravitational deformation. We find that the most significant geological effect is a 5.2 km long alignment of ground ruptures along the Mount Vettore Fault System. These ruptures are independent from lithology, topography, morphology, and change in slope and exhibit an average dip‐slip displacement of ~13 cm. Geometry, kinematics, and dimensional properties of this zone of deformation strongly lead us to favor the primary surface faulting hypothesis that fits well the predicted estimates from experimental scaling law relationships. Our study provides relevant hints for surface faulting in extensional domains, contributing to implement the worldwide database of the moderate earthquakes. Key Points: Detailed documentation of subtle primary coseismic surface faulting induced by moderate magnitude earthquake masked by later seismic event Contribute to the worldwide database of the moderate earthquakes surface faulting events in extensional domains